A 16-channel low-power non-uniform spaced filter bank core for digital hearing aids - Chong, Kwen-Siong (2009)
We describe a 16-channel critical-like spaced, high stopband attenuation (≥60 dB, 109th X 16-order), micropower (247.5 W@1.1 V, 0.96 MHz), small integrated circuit (IC) area (1.62 mm2@0.35- m CMOS) finite impulse response filter bank core for power-critical hearing aids. We achieve the low-power